Simultaneous Tests for Trend and Serial Correlations for Gaussian Markov Residuals - Krishnaiah, P. R.; Murthy, V. K. (Econometrica, 1966)
In the paper, exact tests are proposed for testing the trend in the presence of autocorrelation and also for testing the trend and autocorrelation simultaneously in a first order Markov process. Also, the simultaneous confidence intervals associated with these tests are derived. These results are extended to a higher order Markov process.